Consumption Pattern And Purchase Intention Of Consumers Regarding Organic Food Products :An Empirical Study In Delhi Ncr - Kumar, Dr. Praveen; Sharma, Mr. Sunil; Garg, Mr. Naveen (The journal of contemporary issues in business and government, 2021)
The objectives of this study were to examine the organic food consumption pattern and purchase intention of consumers towards organic food. Respondents were selected by using stratified convenience sampling method. The data was collected from Delhi (National capital Region). Out of 500 respondents personally interviewed, 442 questionnaires were completed and suitable for further analysis. Frequency distribution, percentage and cross tabulation were used as statistical tool to analyze data with the help of SPSS. The finding of the study reveled thatthe consumption of organic products has increased tremendously during last five years.Herbs, spices, pulses, vegetable, fruits and cereals were consumed frequently by the respondents. Specialized organic stores considered as most preferred place to buy organic food followed by karyana store, supermarket, and vegetable market. Majority of respondents come to know about organic food through Word-of-mouth communication followed by specialised organic food store, foreign visits. Internet, newspaper and magazine are major source of information for nutritional and safety updates. Organic India was the most preferred organic brand followed by 24 letter manta, Morarka and Sanjeevani. The study suggested that for improving awareness regarding organic food, the marketers and producers should conduct health campaigns, public lectures, and use print media and internet as effective tool to enhance the awareness about organic food among common people.